Rating mean of expert judges and asymmetric confidence intervals in content validity: An SPSS syntax - Merino-Soto, César; Livia-Segovia, José (Anales de Psicología / Annals of Psychology, 2022)
The estimation of content validity, obtained by rational analysis of expert judges, is usually done with coefficients that standardize between 0.0 and 1.0 the judges’ judgment. However, this estimate can also be expressed in the metric of the judges’ responses, in the form of the response mean, and with asymmetric confidence intervals around this mean. The aim of the present manuscript is to implement a procedure for these estimates (response mean and asymmetric confidence intervals) in a program written in SPSS syntax. The rationale of the procedure is explained, and an applied example of the calculation is developed. The program is freely distributed upon request to the authors.